Quality characterization of green mung bean (Mg 11 (Kintab) (Vigna radiata (L. Wilczek)) starch-based noodles and its potato (Solanumtuberosum (L.)) starch blend at various stages of noodle production - Felix, Dominic Jhon R.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The objective of the study was to characterize the quality of cellophane noodles made from two different blends of starches. These blends were made from starch extracted from pure local mung bean cultivar, and the same local green mung bean starch (GMBS) was blended with potato starch. The noodles were characterized at different material stages of noodle production including the binder, dough, dried, and cooked noodles. The characterization involves total proximate composition, physicochemical (water activity, pH, and Apparent Amylose content), structural (Scanning Electron Microscopy [SEM], Optical Microscopy), pasting (Rapid Visco Analysis [RVA]), and thermal properties (Differential Scanning Calorimetry [DSC]). The GMBS was established to be acidic, have high apparent amylose content, and low water activity. The granule size of the GMBS was measured to have the ranges of 10 to 25 μm across the longest side. The SEM images provided defined the changes in the structural profile of the different material stages of noodle production and it was seen during the dough, where a honeycomb-like structure was formed with starch granules trapped inside the starch matrix, the dried noodle, where the presence of spherulites were seen, and lastly the cooked noodle, where the honeycomb like structure reappeared and had denser matrix. Optical images confirmed the general trend that was observed in the SEM analysis. The addition of PS to the green mung bean starch noodle (GMBSN) formulation exhibited translucent noodle due to its phosphorus content as indicated in the optical microscopy.
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Noodles -- Philippines; Starch -- Philippines; Mung bean -- Philippines